Prevalence of HCV induced diabetes among HCV patients in Punjab Pakistan, A cross-sectional study - Zahid, Sadia; Naveed, Muhammad; Saeed, Sidra (International Journal of Pathology, 2025)
Background: With a high disease burden, hepatitis C virus (HCV) disorders are one of Pakistan’s top public health concerns. Despite the country’s access to efficient antiviral medications, the overall population’s disease burden has not decreased. This may be due to the infection’s asymptomatic character, which makes it difficult to diagnose until late in the course of symptoms. A population-based analysis is required for an efficient control of the virus in order to more precisely figure out and identify HCV infections in the nation. Methods: In our study, 2000 HCV samples were collected from different regions of Punjab and tested for HCV by Bioline™ HCV kit for early detection and Fasting blood glucose level was determined by glucometer to check diabetes. Then all HCV positive samples sent to Genome center for molecular based diagnostics & research (GCMD) Lahore, where samples were confirmed by PCR and diabetes was confirmed by HbA1c test for HCV induced diabetes confirmation. The objective of this study is to find out the overall prevalence of HCV induced diabetic samples among HCV positive patients. Viral load, Hemoglobin levels and platelets count were other factors analyzed in this research contributing to the effective prevention, control and treatment to control HCV induced diabetes prevalence in the province of Punjab Pakistan. Results: Overall, 80% of the samples were detected as HCV positive and HCV induced diabetic samples were 9% that were identified in this study. A significant difference in prevalence of HCV induced diabetes was observed in different age groups among (male and female) with 57% male and 43% female patients. Conclusion: This study represents the prevalence of HCV induced diabetes among HCV infected patients of about 9% (age 22-72 years) from different regions of Punjab.